2022
DOI: 10.1183/16000617.0208-2021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and applications of oscillometry

Abstract: Recently, “Technical standards for respiratory oscillometry” was published, which reviewed the physiological basis of oscillometric measures and detailed the technical factors related to equipment and test performance, quality assurance and reporting of results. Here we present a review of the clinical significance and applications of oscillometry. We briefly review the physiological principles of oscillometry and the basics of oscillometry interpretation, and then describe what is currently known about oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 235 publications
4
82
1
2
Order By: Relevance
“…One study showed that there was a poor correlation between the lung function index of SAD and gas trapping (FVC and RV/TLC) ( Sorkness et al, 2008 ), and its ability to evaluate SAD may be questioned. Compared with spirometry, the frequency dependence of R rs of IOS was commonly quantified as the difference R 5 -R 20 ( Kaminsky et al, 2022 ). A recent study confirmed that R 5 -R 20 was a direct indicator of anatomical narrowing in the small airways through lung computational models ( Foy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that there was a poor correlation between the lung function index of SAD and gas trapping (FVC and RV/TLC) ( Sorkness et al, 2008 ), and its ability to evaluate SAD may be questioned. Compared with spirometry, the frequency dependence of R rs of IOS was commonly quantified as the difference R 5 -R 20 ( Kaminsky et al, 2022 ). A recent study confirmed that R 5 -R 20 was a direct indicator of anatomical narrowing in the small airways through lung computational models ( Foy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It does not require the patient's special cooperation and is simple, noninvasive, repeatable, and provides comprehensive respiratory physiological parameters. It is especially suitable for people aged 3 and above [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, impulse oscillometry (IOS) is an effort-independent modality based on the well-described forced oscillation technique (FOT) ( 9 , 10 ) and has emerged as a method to measure pulmonary function in both children and adults ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%